2008
DOI: 10.1103/physrevstab.11.040401
|View full text |Cite
|
Sign up to set email alerts
|

Modeling particle emission and power flow in pulsed-power driven, nonuniform transmission lines

Abstract: Pulsed-power driven x-ray radiographic systems are being developed to operate at higher power in an effort to increase source brightness and penetration power. Essential to the design of these systems is a thorough understanding of electron power flow in the transmission line that couples the pulsed-power driver to the load. In this paper, analytic theory and fully relativistic particle-in-cell simulations are used to model power flow in several experimental transmission-line geometries fielded on Sandia Natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 26 publications
0
19
0
2
Order By: Relevance
“…The thresholds are a function of the material and its preparation. A typical values for accelerator cathodes range from 150 to 250 kV=cm [9]. The value may be determined by the departure of the transmission line current from their vacuum values, for example when OF exceeds IF.…”
Section: A Simulation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…The thresholds are a function of the material and its preparation. A typical values for accelerator cathodes range from 150 to 250 kV=cm [9]. The value may be determined by the departure of the transmission line current from their vacuum values, for example when OF exceeds IF.…”
Section: A Simulation Detailsmentioning
confidence: 99%
“…To determine the suitability of the self-magnetic-pinch (SMP) diode [1][2][3][4][5][6] as a radiographic source, an experimental campaign was conducted on Sandia's RITS-6 accelerator [7][8][9] to quantify its shot-toshot variation. The accelerator operated at 4.5 MV and the SMP diode was fielded with changes only to the anodecathode (AK) gap and cathode needle radius (r c ).…”
Section: Introductionmentioning
confidence: 99%
“…The dustbin introduces a further difficulty. It was observed that during the flow, resonant cavity modes develop in it, which interact with the flow, causing unwanted oscillations [13].…”
mentioning
confidence: 99%
“…It was recently shown that the sheath flow is symmetric and regular even for an asymmetric power-generating machine [13]. Even when azimuthal symmetry is assumed, attempts to direct the current around the knob toward the diode resulted in turbulent flow [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation